1986
DOI: 10.2183/pjab.62.98
|View full text |Cite
|
Sign up to set email alerts
|

Association of a viroid-like RNA from plum dapple disease occurring in Japan.

Abstract: Introduction. Plum dapple disease is a newly described disease by Terai (1985) 3) in Japanese Plum (Prunes salicina Lindley cv. Taiyo) cultivated in Yamanashi Prefecture, Japan. The infected trees produce dapple fruits with faint reddish and chlorotic blotches, but no visible symptom is recognized on the leaves and stems. The disease is transmissible by grafting, however, the causal agent has not yet known. In this paper, we describe detection and some properties of a viroid-like RNA associated with plum dappl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Taiyo, has an Mr similar to that of hop stunt viroid (HSV)-grapevine and has a relatively high sequence homology with the HSV group (Sano et aL, 1986b).…”
Section: Introductionmentioning
confidence: 99%
“…Taiyo, has an Mr similar to that of hop stunt viroid (HSV)-grapevine and has a relatively high sequence homology with the HSV group (Sano et aL, 1986b).…”
Section: Introductionmentioning
confidence: 99%
“…Only some P. salicina cultivars such as Angeleno and Taiyo displayed some transient discoloration on the fruits and these symptoms disappeared at maturity. It cannot yet be confirmed that HSVd is responsible for dapple plum, since both the original Taiyo PR72 cultivar from Japan in which this association was established (Sano et al, 1986), and the Angeleno 892 cultivar from Italy (Giunchedi et al, 1997) were doubly infected by HSVd and the agent of PRMa. The natural manner of transmission of HSVd in Prunus is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hop stunt viroid (HSVd) was identified on Japanese plum (Prunus salicina) cv. Taiyo for the first time in Japan (Sano et al, 1986). The disease symptoms, ringshaped discolorations, are obvious only on fruits with a red skin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, viroids have only been found in higher plants [2,20]. Recent investigations have shown that in certain non-herbaceous crop plants such as citrus, grapefruit, plum, and grapevine, various viroids are present in such minute amounts [3,4,8,10,14,[16][17][18] that their isolation, purification and subsequent direct sequence analysis is rather cumbersome, if not practically impossible. If successful at all [3] the transmission of such viroids to and their propagation in herbaceous plants can be problematic because it may lead to the selection of sequence variants which differ from the viroid predominating in the original non-herbaceous host plant [ 12].…”
mentioning
confidence: 99%
“…The resulting double-stranded cDNA is purified by PAGE and then sequenced chemically [11]. We applied this whole procedure to the sequence analysis of hop stunt viroid (HSVd) [6], which has been found to be present worldwide in many plant species [8,10,14,[16][17][18].…”
mentioning
confidence: 99%